2018
DOI: 10.3389/fimmu.2018.01010
|View full text |Cite
|
Sign up to set email alerts
|

C5a Blockade Increases Regulatory T Cell Numbers and Protects Against Microvascular Loss and Epithelial Damage in Mouse Airway Allografts

Abstract: Microvascular injury during acute rejection has been associated with massive infiltration of CD4+ T effector cells, and the formation of complement products (C3a and C5a). Regulatory T cells (Tregs) are potent immunosuppressors of the adaptive immune system and have proven sufficient to rescue microvascular impairments. Targeting C5a has been linked with improved microvascular recovery, but its effects on the Treg and T effector balance is less well known. Here, we demonstrate the impact of C5a blockade on Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 75 publications
1
52
0
Order By: Relevance
“…Further, studies with adoptive transfer of T cells from WT mice into C3aR −/− and C5aR −/− mice supported the notion that ablation of C3aR and C5aR mediated signaling to affect the complement and T‐cell interaction and subsequent downregulation of costimulatory molecules and IL‐6, while upregulation of IL‐10 and systemic Tregs generation during alloimmune inflammation . Recently, targeted blockade of complement C5a was found sufficient to induce peripheral and graft CD4 + FOXP3 + Tregs and augmented the microvascular blood flow between donor and recipients grafts, which resulted in suppression of subepithelial collagen deposition during rejection . These findings supported the notion that C5a blockade, anti‐C5a‐C5aR ligation, shifted the immune balance toward Treg phenotype, which favored the reparative phase through the secretion of various cytokines (IL‐10, IL‐5, and TGF‐β) .…”
Section: Complement Factor and T‐regulatory Cell Interactionsmentioning
confidence: 88%
See 4 more Smart Citations
“…Further, studies with adoptive transfer of T cells from WT mice into C3aR −/− and C5aR −/− mice supported the notion that ablation of C3aR and C5aR mediated signaling to affect the complement and T‐cell interaction and subsequent downregulation of costimulatory molecules and IL‐6, while upregulation of IL‐10 and systemic Tregs generation during alloimmune inflammation . Recently, targeted blockade of complement C5a was found sufficient to induce peripheral and graft CD4 + FOXP3 + Tregs and augmented the microvascular blood flow between donor and recipients grafts, which resulted in suppression of subepithelial collagen deposition during rejection . These findings supported the notion that C5a blockade, anti‐C5a‐C5aR ligation, shifted the immune balance toward Treg phenotype, which favored the reparative phase through the secretion of various cytokines (IL‐10, IL‐5, and TGF‐β) .…”
Section: Complement Factor and T‐regulatory Cell Interactionsmentioning
confidence: 88%
“…A number of preclinical and clinical studies have identified crucial roles of active complement proteins, such as C1q, C3b/iC3b, C3a (and C3aR), and C5a (and C5aR) in T‐cell response during homeostasis and disease, which affect T‐ cell function via APCs, the cytokine milieu, or downstream complement activation products . The release of C3, fB, and fD, as well as C5, and upregulation of C3aR and C5aR have been reported during cognate interactions between T cells and APCs (macrophages and DCs), which are induced through CD28/CD80/CD86 and CD154/CD40 molecular signaling on the membrane of APCs . Considering the involvement of complement‐mediated costimulation of T cells and development of new complement inhibitors suggested that the therapeutic use of costimulation blockade through complement inhibitors has been under preclinical and clinical testing to improve graft injuries while minimizing global suppression of protective immunity, which could become a valuable therapeutic step for transplant patients in combination therapies.…”
Section: Complement and Costimulatory Signalsmentioning
confidence: 99%
See 3 more Smart Citations